ACCIDENTAL INGESTION OF CYLINDRICAL BATTERIES IN CHILDREN - INTERVENTIONAL OR CONSERVATIVE MANAGEMENT? - Gabriela Păduraru; Andreea-Mădălina Nichita; Florin Filip; Elena Tataranu; Smaranda Diaconescu (Amaltea Medical Publishing House, 2021)
Ingestion of cylindrical batteries is a rare condition in children. There are no clear guidelines regarding the appropriate management of this condition. We present 2 such cases; one patient required endoscopic removal of the battery, while in the other one the battery passed spontaneously. We recommend that such cases be admitted for monitoring and treated on an individual basis, according to the clinical picture, X-ray data and the availability of pediatric emergency endoscopy.